2020
DOI: 10.7759/cureus.10307
|View full text |Cite
|
Sign up to set email alerts
|

Does an Incidental Meckel's Diverticulum Warrant Resection?

Abstract: Meckel's diverticulum (MD) is the most common gastrointestinal malformation. The management of symptomatic Meckel's diverticulum has been undecidedly resection; however, the management of incidental Meckel's diverticulum has been fraught in comparison. As a systematic literature review, PubMed, PubMed Central (PMC), and MEDLINE were used. The search phrase utilized was "Meckel Diverticulum/Surgery [Mesh]" and resection incidental. The search was completed on July 18, 2020 and was limited to 1980 until the day … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 29 publications
0
11
0
3
Order By: Relevance
“…In our study, the mean length of the diverticulum was 55.21 cm (SD 26.37), supporting the fact that longer diverticula are more liable to develop complications. [4][5][6][7].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the mean length of the diverticulum was 55.21 cm (SD 26.37), supporting the fact that longer diverticula are more liable to develop complications. [4][5][6][7].…”
Section: Discussionmentioning
confidence: 99%
“…In the case reported herein, video-surgery was not an option due to unavailability in the unit. The presence of the diverticulum is usually an incidental diagnosis, and its resection is debatable when asymptomatic [7] , [11] . When complications arise, such as torsion, obstruction, volvulus or perforation, its removal is mandatory.…”
Section: Discussionmentioning
confidence: 99%
“…A literature review motivated authors to compile the main reasons that justify a resection of Meckel's diverticula found accidentally, based on factors that would increase the risk of future complications, such as patients 50 years old or younger, male, presence of a diverticulum greater than 2 cm wide, proof of the existing ectopic mucosa, narrow base aspect, and connection of the diverticulum with the umbilical scar through a connective tissue (relative indication). On the other hand, there are situations that discourage such intervention, including patients with advanced age, diffuse or local peritonitis, perforation of the appendix or intestinal loop, damage to other abdominal organs and patients who were victims of trauma in multiple organs [7] , [8] , [13] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 We agree entirely on this point and would like to add a recent observation from the systemic review that there is a recent shift in the evidence towards prophylactic resection of Meckel's diverticulum. 4…”
mentioning
confidence: 99%